Sanctions Pressure on the Russian Economy: Ways to Overcome the Costs and Benefits of Confrontation within the Framework of Import Substitution - M. R. Safiullin; L. A. Elshin (Финансы: теория и практика)
The sustainable development of the national economy, taking into account the creation of mechanisms for ensuring economic security, technological sovereignty and preventing threats to the localization of import supplies of final and intermediate consumption goods, is one of the priority directions of economic policy in the conditions of systemic restrictions formed under the pressure of sanctions. In this regard, the study of the key externalities generated within the framework of the sanctions confrontation is an extremely popular task, both for science and practice. In this paper, the authors pay attention to both the actualization of the problem posed and an overview of some of the costs and benefits that can be extracted in the new reality for the national economic system of the Russian Federation. The main purpose of the study is to systematize and analyze the key parameters of economic growth in the Russian Federation under the sanctions pressure of the 2022 model and substantiate the policy of intensification of import substitution as a key mechanism for ensuring sustainable development in the medium and long term in the new reality. The subject of the study is the restrictions imposed by a number of Western countries in relation to the Russian economy, the costs they generate and the opportunities for building a new model of economic growth. As the main results of the study, it is necessary to highlight the systematization of sanctions and restrictions imposed on Russia in 2022; identified trends in the formation of key macroeconomic parameters of the Russian economy, revealing the features of labor market development, GDP formation, investment and business activity, etc.; systematization of risks and prospects of economic growth, including the projection of theoretical models of economic dynamics (IS-LM, AD-AS) on the received estimates; identification of the dependence of the national economy of the Russian Federation on the import of technologies and intermediate/final consumption goods, followed by justification and development of a model to stimulate the policy of import substitution within the framework of the activation of NTR.